Forage and breed effects on behavior and temperament of pregnant beef heifers - Mays, Angela R (BioMed Central, 2013)
BACKGROUND: Integration of behavioral observations with traditional selection schemes may lead to enhanced animal well-being and more profitable forage-based cattle production systems. Brahman-influenced (BR; n = 64) and Gelbvieh × Angus (GA; n = 64) heifers consumed either toxic endophyte-infected tall fescue (E+) or one of two nontoxic endophyte-infected tall fescue (NT) cultivars during two yr. Heifers were weighed at midpoint and termination of grazing. Grazing behavior (grazing, resting in the shade, lying, or standing without grazing) was recorded (n = 13 visual observations per yr in June and July) for each pasture. During yr 2, exit velocity (EV) and serum prolactin (PRL) were determined. RESULTS: Grazing behavior was influenced (P < 0.05) by an interaction between fescue cultivar and breed type. Gelbvieh × Angus heifers assigned to E+ pastures had the lowest percentage of animals grazing and the largest percentage of animals resting in the shade. Brahman-influenced heifers had faster EV (P < 0.001) than GA heifers (0.52 vs. 0.74 ± 0.04 s/m, respectively). Body weight (BW) was affected (P < 0.01) by an interaction of tall fescue cultivar and d, and an interaction of tall fescue cultivar and breed type. Heifers grazing NT pastures were heavier (P < 0.01) than heifers grazing E+ pastures at midpoint and termination. Gelbvieh × Angus heifers grazing NT pastures were heavier (P < 0.01) than GA and BR heifers grazing E+ and BR heifers grazing NT pastures. An interaction of forage cultivar and breed type occurred on serum PRL (P < 0.01). CONCLUSION: Collectively fescue cultivar, EV, and concentrations of serum PRL were associated with grazing behavior. Heifers grazing NT pastures were observed to be grazing more than heifers assigned to E+ pastures, regardless of breed type, which may have contributed to changes in BW and average daily gain (ADG) in heifers. Integration of behavioral observations along with traditional selection schemes may lead to enhanced animal well-being and more profitable forage-based cattle production systems.